Variability in potentially preventable hospitalisations: an observational study of clinical practice patterns of general practitioners and care outcomes in the Basque Country (Spain). Issue 5 (18th May 2015) - Orueta, Juan F; García-Alvarez, Arturo; Grandes, Gonzalo; Nuño-Solinís, Roberto
Abstract : Objectives: To explain the variability in the frequency of potentially preventable hospitalisations (ambulatory care sensitive conditions, ACSCs) based on factors at multiple levels (individual, health professional, health centre and health district), and specifically using resource efficiency indicators for general practitioners (GPs). Design: Cross-sectional study. We analysed primary care electronic health records and hospital discharge data using multilevel mixed models. Setting: Primary care network of the Basque Health Service (Spain). Participants: All the residents in the Basque Country ≥14 years of age, covered by the public healthcare system (n=1 959 682), and all the GPs (n=1193) and health centres (n=130). Main outcome measures: Individuals admitted for ACSCs, over a 12- month period. Results: Admissions for ACSCs were less frequent among patients who were female, middle-aged or from the highest socioeconomic classes. The health centre variables considered and GP list size were not found to be significant. After adjusting for the variables studied including morbidity, the risk of hospital admission was higher among individuals under the care of GPs with greater than expected numbers of patient visits and prescribing costs (OR=1.27 (95% CI 1.18 to 1.37); 1.16 (1.08 to 1.25)), and who make fewer referrals than the mean among their colleagues (OR=1.33 (1.22 to 1.44)). Conclusions: When assessing activities and procedure indicators in primary care, we should also define outcome-based criteria. Specifically, GPs who are repeatedly visited by their patients, have higher prescribing costs and are more reluctant to refer patients to specialists obtain poorer outcomes.